Tracheal Stenosis following Percutaneous Dilatational Trache-Ostomy using the Single Tapered Dilator: An MRI Study. Issue 6 (November 2014) - Young, E.; Pugh, R.; Hanlon, R.; O'Callaghan, E.; Wright, C.; Jeanrenaud, P.; Jones, T. M.; Dempsey, G. A.
Despite widespread adoption of percutaneous dilatational tracheostomy within the critical care setting, there is still uncertainty regarding long-term complications, particularly in relation to missed or subclinical tracheal stenosis. In this study, all patients underwent tracheostomy using a single tapered dilator ≥ three months prior to enrolment and were evaluated using magnetic resonance imaging, spirometry and questionnaire. Tracheal area was recorded and deemed to be stenotic if a reduction of ≥10% was found. Fifty patients underwent magnetic resonance imaging and 49 attended for interview. Five patients were diagnosed with tracheal stenosis—none were symptomatic. Six of the 50 tracheostomies were technically difficult. Spirometry was not predictive of stenosis. A post critical care exercise tolerance of less than 100 metres was found in four tracheal stenosis patients. The prevalence of subclinical tracheal stenosis following percutaneous tracheostomy is low, with limited clinical significance. No patients required corrective surgery for tracheal stenosis. Routine airway follow-up in asymptomatic patients appears to be unwarranted.